2015
DOI: 10.1038/nchembio.1926
|View full text |Cite
|
Sign up to set email alerts
|

Translocation-coupled DNA cleavage by the Type ISP restriction-modification enzymes

Abstract: Endonucleolytic double-strand DNA break production requires separate strand cleavage events. Although catalytic mechanisms for simple dimeric endonucleases are available, there are many complex nuclease machines which are poorly understood in comparison. Here we studied the single polypeptide Type ISP restriction-modification (RM) enzymes, which cleave random DNA between distant target sites when two enzymes collide following convergent ATP-driven translocation. We report the 2.7 Angstroms resolution X-ray cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(73 citation statements)
references
References 60 publications
5
68
0
Order By: Relevance
“…Here we describe experiments on the multidomain and multifunctional s ingle p olypeptide Type I SP restriction endonucleases, as exemplified by LlaGI and LlaBIII from Lactococcus lactis ( 6 , 7 ). Rather than being able to directly dimerise, structural and biochemical studies predict that Type ISP nuclease monomers are held at least 30 bp apart ( 8 ). To produce a dsDNA break it was suggested that the enzyme complex moves back-and-forth on the DNA while introducing multiple nicks, eventually shredding the DNA.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Here we describe experiments on the multidomain and multifunctional s ingle p olypeptide Type I SP restriction endonucleases, as exemplified by LlaGI and LlaBIII from Lactococcus lactis ( 6 , 7 ). Rather than being able to directly dimerise, structural and biochemical studies predict that Type ISP nuclease monomers are held at least 30 bp apart ( 8 ). To produce a dsDNA break it was suggested that the enzyme complex moves back-and-forth on the DNA while introducing multiple nicks, eventually shredding the DNA.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid this, Type ISP endonucleases control their nuclease activity using long-range communication. Where there are a pair of unmodified targets in a head-to-head (HtH) orientation on foreign DNA, dsDNA breaks are produced at random, non-specific locations, with the majority between the sites ( 8 11 ). However, for every pair of HtH sites on newly-replicated host DNA, one target will retain methylation from the parental strand.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations